Optimalisasi Kompetensi Akuntansi melalui Pelatihan Aplikasi Accurate bagi Siswa dan Guru di SMK Taruna 1 Padang - Mustika, Rasyidah; Wirahadi Ahmad, Afridian; Dwiharyadi, Anda; Endrawati, Endrawati; Santi, Elfitri (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2024)
The training on the use of Accurate software at SMK Taruna 1 Padang aims to enhance the competence and professionalism of accounting students and teachers in preparing digital financial statements. This activity is part of a community service program conducted by a team of lecturers from Politeknik Negeri Padang (PNP). Accurate Accounting, known as a user-friendly accounting software, is widely used in the industry for preparing financial reports in service, trading, and manufacturing companies. The software is also aligned with Indonesian tax regulations, making it a vital skill for SMK graduates entering the workforce. The training was attended by 22 students and 2 teachers from SMK Taruna 1 Padang. One of the identified challenges is the absence of a specific curriculum teaching the use of Accurate at the school, which could leave graduates lacking relevant skills for industry demands. Therefore, this training was designed to bridge that gap, focusing on mastering the use of Accurate Accounting in preparing corporate financial statements. The results of the training have successfully improved the technical skills of both students and teachers in operating the accounting software. Furthermore, the outcomes of this program include training modules, tutorial videos, media publications, and scientific article publications in national journals. It is hoped that these efforts will support the development of accounting competencies among students and strengthen the professionalism of teachers at SMK Taruna 1 Padang.